FROM FACTOR PRICES EQUALIZATION TO OUTPUT PRICES EQUALIZATION - Teguh Santoso; Maruto Umar Basuki (JURNAL DINAMIKA EKONOMI PEMBANGUNAN, 2012)
This paper is addresses to see how the impact of the factor price equalization in product pricesequalization. According to Heckser-Ohlin (H-O) model, trade in goods will cause the absolute and relativeprices of factor between counties to move toward equality. If free trade occurs, factor prices between countrieswill not different when countries producing the same mix of product with the same technologies and the sameproduct price must have the same factor prices. Product prices equalization will occur when the countrieshave same set unit value isoquant (UVI) and, as well under CRS condition MPL and MPk are constant alongexpansion paths of each industries